An ethnozoological study of Vespa magnifica with special reference to hunting by Nyishi tribes of Arunachal Pradesh, India. - Dobiam Narba; Leki Wangchu; Dobiam Tagam (Dera Natung Government College Research Journal)
Many tribes of Arunachal Pradesh consider the hornet Vespa magnifica as highly delicious and seasonal food with high economic value. The hunting practices of these hornets are an age-old tradition that has been passed down from generation after generations. Unfortunately, nowadays many new methods of hunting these hornets have emerged like the use of DDT, Kerosene, Diesel and Bleaching powder. Due to these practices the sightings and hunting of hornets has declined. The present study provides a documentation of the traditional hunting techniques of these hornets in Lower Subansiri District of Arunachal Pradesh and suggests a more sustainable approach to maintain the rich economic, diet and diversity value of these hornets.